A Review on Bioactive Phytochemical Constituents and Pharmacological Activities of Aegiceras corniculatum: A Pharmaceutically Important Mangrove Plant - Pritam Sarkar; Tasfiya Rufaidah Ahnaf; Razina Rouf; Jamil Ahmad Shilpi; Shaikh Jamal Uddin (Journal of Chemistry)
Aegiceras corniculatum, commonly referred to as Khalsi, is a member of the mangrove Myrsinaceae family. The various parts of this plant have been used in traditional medicinal systems for their potential therapeutic effects in conditions such as asthma, microbial infections, diabetes, pain relief, inflammation, cancer, and arthritis. A diverse array of bioactive phytochemicals such as flavonoids, benzoquinones, triterpenes, polyphenolic acids, stilbenes, tannins, and macrolides have been identified in different parts of this plant. The aim of this review was to summarize the bioactive phytoconstituents reported from this plant that are accountable for the observed different pharmacological effects of the plant and further elucidate the possible underlying mechanisms by which these chemicals exert their actions. The search was conducted on various widely used database platforms, including Google Scholar, Scopus, Web of Science, SciFinder, and PubMed. Articles published until July 2023 were extracted and all the information was sorted based on the inclusion and exclusion criteria. The data revealed that anti-inflammatory compounds from this plant suppress iNOS, myeloperoxidase, COX, LOX, and cytokines (like TNF-alpha, IL-1ß, LTB4, IL-12, and IL-6) to reduce inflammation. 5-O-Butyl-embelin, 2-hydroxy-5-ethoxy-3-nonyl1, 4-benzoquinone, 5-O-methylembelin, 5-O-methyl-rapanone, s-saponin, and 5-O-ethylembelin are some phytochemicals of A. corniculatum with anticancer properties, although their mechanism is unclear. A. corniculatum has antibacterial, parasitic, and antifungal effects, but no antiviral effects were reported. The plant-isolated coumaric acid and fatty acids interact with bacterial DNA/RNA and limit protein formation, making them antibacterial. Gallocatechin, epicatechin, epigallocatechin-3-O-gallate, epigallocatechin, and other tannins, as well as flavonoids like kaempferol, quercetin, and isorhamnetin, are some of the compounds in A. corniculatum that may depolarize and change bacterial membranes, showing antibacterial effect. These phenolic chemicals also reduce oxidative stress and help treat cancer and other inflammatory diseases. The extract of this plant activates the κ-opioid receptor, causing central antinociception. Catechol components, such as epigallocatechin-3-O-gallate, protect against CNS illnesses including Parkinson’s disease and amnesia. Despite numerous studies demonstrating various pharmacological advantages of this plant and its constituents, the number of clinical trials conducted on humans remains significantly limited.